Evaluation of two surgical methods for maxillary hypoplasia in patients with cleft lip and palate - GUO Songsong, ZHANG Zhenxing, ZHANG Ping, JIANG Chenghui, CHENG Jie, JIANG Hongbing, LI Sheng (Kouqiang yixue)
Objective To evaluate the clinical efficacy of anterior maxillary segmental distraction osteogenesis and Le Fort Ⅰ Osteotomy on secondary maxillary hypoplasia in patients with cleft lip and palate. Methods Twenty-five patients with maxillary hypoplasia secondary to cleft lip and palate underwent surgery in maxillofacial surgical department of the Affiliated Stomatological Hospital of Nanjing Medical University were selected. Ten cases were treated using tooth-borne distractors for anterior maxillary distraction osteogenesis, and fifteen cases underwent Le Fort Ⅰ Osteotomy. Cone-beam CT, positive and lateral features, speech recording and nasopharyngeal fibroscope were taken one week before operation and one month after surgery. The clinical outcomes of the two methods and their influence on patients’ speech function were measured and compared using t-test. Results Both techniques effectively advanced the maxilla and significantly improved the patients’ profiles. Anterior maxillary segmental distraction osteogenesis, which was economical and minimally invasive, greater advanced the maxilla. However, the postoperative profile was better in patients undergoing Le Fort I osteotomy, with statistically significant differences (P<0.05). Neither technique significantly affected speech, but Le Fort Ⅰ osteotomy had a greater impact on palatopharyngeal anatomy, indicated by increased soft palate length (2.01±1.71)mm, reduced thickness (0.98±0.50) mm, and increased pharyngeal depth (3.06±1.35) mm, with statistically significant differences (P<0.05). Conclusion Anterior maxillary segmental distraction osteogenesis and orthognathic surgery are both effective methods for the treatment of secondary maxillary hypoplasia in cleft lip and palate patients. Anterior maxillary distraction osteogenesis has advantages over Le Fort I osteotomy in terms of economic benefits and its impact on the soft palate structure.